PENGARUH SOSIALISASI, SANKSI, SISTEM E-FILING, TARIF, DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK - Dewi, Neng Rosita; Asalam, Argan Gani (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021, 2021)
In Indonesia, the largest income is through taxes to finance various state needs. Especially in the APBN, there is an important role that is owned by taxes, but tax revenues in the APBN in Indonesia have not been maximized. With not maximal tax revenue in Indonesia, discipline, awareness and compliance of taxpayers is very much needed to comply with applicable tax obligations. The purpose of this research is to be able to see the effect of socialization, sanctions, e-filing system, tariffs and quality of tax services on the compliance of individual UMKM taxpayers. This research uses quantitative primary data techniques. The population in this research is individual UMKM taxpayers registered at (KPP) Pratama Cimahi 2020 using convenience sampling and the sample used is 100 samples. This research uses a questionnaire with a Likert scale of 1-5 as the collection method. This research was analyzed using descriptive statistical analysis and multiple linear regression analysis. The results in this research state that socialization, sanctions, e-filing system, tariffs and quality of tax service services simultaneously (simultaneously) have a significant correlation to taxpayer compliance. In addition, the variables of socialization, sanctions and tariffs separately (partial) have a significant positive correlation with taxpayer compliance, but the variables of the e-filing system and service quality of the tax authorities separately (partial) do not have a significant correlation with taxpayer compliance